Staying at the crossroads: assessment of the potential of serum lithium monitoring in predicting an ideal lithium dose - Lima,Thiago Zaqueu (2008)
OBJECTIVE: Lithium has been successfully employed to treat bipolar disorder for decades, and recently, was shown to attenuate the symptoms of other pathologies such as Alzheimer's disease, Down's syndrome, ischemic processes, and glutamate-mediated excitotoxicity. However, lithium's narrow therapeutic range limits its broader use. Therefore, the development of methods to better predict its dose becomes essential to an ideal therapy. METHOD: the performance of adult Wistar rats was evaluated at the open field and elevated plus maze after a six weeks treatment with chow supplemented with 0.255%, or 0.383% of lithium chloride, or normal feed. Thereafter, blood samples were collected to measure the serum lithium concentration. RESULTS: Animals fed with 0.255% lithium chloride supplemented chow presented a higher rearing frequency at the open field, and higher frequency of arms entrance at the elevated plus maze than animals fed with a 50% higher lithium dose presented. Nevertheless, both groups presented similar lithium plasmatic concentration. DISCUSSION: different behaviors induced by both lithium doses suggest that these animals had different lithium distribution in their brains that was not detected by lithium serum measurement. CONCLUSION: serum lithium concentration measurements do not seem to provide sufficient precision to support its use as predictive of behaviors.